DEVELOPING STUDENTS' FUNCTIONAL LITERACY IN PRIMARY EDUCATION THROUGH METACOGNITIVE AND INQUIRY-BASED APPROACHES (Journal of Universal Science Research, 2026)
This article theoretically and practically analyzes the integrative potential of metacognitive and inquiry-based approaches in developing primary school students' functional literacy. The modern educational paradigm requires not only the acquisition of knowledge but also the ability to apply it in real-life situations, solve problems independently, and manage one’s own cognitive activity